Analisis Kebijakan Pendaftaran Tanah Sistematis Lengkap dan Implikasinya terhadap Pembangunan Berkelanjutan di Kota Baubau - Salma, Salma; Asiri, La; Lawelai, Herman (Jurnal Pemerintahan dan Politik, 2024)
This study aims to examine the Complete Systematic Land Registration (CSLR) policy in Baubau City and its impact on sustainable development. This study used qualitative methods by using interviews, document analysis, and field observations to collect data. A sample of respondents consisting of government officials, community members, and community leaders was selected by purposive sampling. Based on the analysis conducted, this study concludes that the successful implementation of CSLR policies in Baubau City has significant implications for sustainable development, including inclusive economic growth, social stability, and increased community participation in the regional development process. Understanding the dynamics of this policy can assist the government and stakeholders in implementing appropriate measures to ensure its sustainable benefits to the people and environment in the city. This research makes a significant contribution to the field of public policy and sustainable development by increasing understanding of policy effectiveness approaches in the context of land registration policies at the local level. This research also provides insight into the factors that influence the successful implementation of CSLR policies. However, this study on CSLR policy and sustainable development in Baubau City has some limitations. The study focuses only on policy aspects without considering the perspectives of local communities, who have unique knowledge and experience and can provide valuable insights into policy implications. Therefore, future research needs to expand the scope of analysis to include policy results, implementation processes, and constraints faced by policy implementers and the public.